Algerophilus, a neglected lineage of Western Mediterranean centipedes (Chilopoda: Geophilidae) - Bonato, Lucio; Voigtländer, Karin; Minelli, Alessandro (Zootaxa, 2012)
Among the diverse geophilomorph centipedes inhabiting the Mediterranean region, we recognise and describe a morpho-logically distinct lineage that has long been misunderstood and neglected. This lineage, which deserves to be treated as adistinct genus (Algerophilus Brolemann, 1925), is broadly similar to Geophilus Leach, 1814 and Tuoba Chamberlin, 1920,but differs from them mainly in the more elongate head and forcipular segment and the coxal pores clustered into elonga-ted pouches. All published and new records are from Western Mediterranean regions including the Baetic Mountains, Ibi-za, the Atlantic Moroccan coastal plain, and the Tell Atlas. A single species A. hispanicus (Meinert, 1870) (=Nesogeophilus mateui Machado, 1953, syn. n.) is recognised on morphological characters, but some geographical varia-tion has been detected in the relative elongation of antennae and forcipules and in the number of trunk segments. The evo-lutionary distinctness and geographical distribution highlighted here for Algerophilus mirror those of other divergent lineages of soil arthropods that are endemic to the Western Mediterranean region.